Load levels in vineyards of malbec cv. and their efects on evolution and fenolic maturation Níveis de produção em vinhedos de altitude da cv. malbec e seus efeitos sobre os compostos fenólicos - Da Silva L.C.* (2008)
The present work had as objective to get information on the phenolic compounds evolution and anthocyanin contents in the berries of grapes, in accordance with the level of clusters thinning, during the maturation to establish criteria that contribute to define the most appropriate management to the vineyard. This experiment was carried out in 2005/06 and 2006/07 seasons, in a commercial vineyard of Villa Francioni in São Joaquim city, State of Santa Catarina, Southern Brazil. The 'Malbec' vineyard was carried in a vertical trellis system, in a 3,0m x 1,2m spacing and covering. The levels of clusters thinning, adjusted in the "véraison," corresponded to 13 t ha-1 (Control), 11 t ha-1 (T1), 9 t ha-1 (T2) and 7 t ha-1 (T3). It was evaluated the evolution of phenolic content during the eight antecedent weeks of harvest on the effect of the three levels of clusters thinning in the quality of the berries. The results showed that, in altitude conditions, the practical of clusters thinning influences in the phenolic content of the 'Malbec' berries. The level production of 10 t ha -1, increased the phenolic and anthocyanin contents, favorable attributes to the production of ample and structuralized wines.